Effect of Pollen-Specific Sublingual Immunotherapy on Oral Allergy Syndrome - Karl-Christian Bergmann, MD; Hendrik Wolf, PhD; Jörg Schnitker, PhD (World Allergy Organization Journal, 2008)
Background Oral allergy syndrome (OAS) triggered by fruit and vegetables often occurs in patients with pollen-induced rhinoconjunctivitis because of cross-reactive epitopes in pollen and associated foods. This open observational study examined the effect of pollen-specific sublingual immunotherapy ([SLIT] B. U. Pangramin or SLITone involving birch/alder/hazel, grasses/rye, and/or mugwort) on OAS triggered by several foods in patients treated in standard practice. Very few studies have examined SLIT use in this situation.Methods Patients (n = 102) had pollen-induced rhinoconjunctivitis and OAS and were followed for up to 12 months. Baseline OAS (triggers, symptoms, and symptom severity) was assessed by questionnaire and patient history. Change in OAS was assessed using oral challenge test with 1 or 2 dominant food triggers (and compared with the sum score calculated from the OAS questionnaire at baseline) and clinician ratings of change. Pollen-induced rhinoconjunctivitis symptoms and medication use were also measured.Results In the oral challenge test, 77.0% of patients were considered responders (decrease in sum score of ≥ 50%; no difference in patients receiving B. U. Pangramin or SLITone). At baseline, investigators rated OAS severity as at least moderate in 94.9% of patients compared with 36.9% after 12 months of treatment. After 12 months, OAS was rated as much or very much improved in 72.9% of patients. Sublingual immunotherapy significantly reduced rhinoconjunctivitis symptoms and medication use. Only 10% of patients experienced adverse drug reactions.Conclusion This study supplements the sparse literature on this topic and suggests that pollen-specific SLIT can reduce OAS triggered by pollen-associated foods in patients with pollen-induced rhinoconjunctivitis. Keywords: immunotherapy, oral allergy syndrome, pollen, rhinoconjunctivitis, sublingual